POTENTIAL OF CATIONIC LIPOSOMES AND CHITOSAN NANOPARTICLES FOR DELIVERY DNA VACCINE MODEL NTC8685-EGFP - Lalu Unsunnidhal (Politeknik Medica Farma Husada Mataram, 2019)
The development of livestock vaccines has important significance in preventing livestock industry losses due to infectious diseases. DNA vaccines that have the potential as a preventive effort against viral diseases have a weakness in the form of low efficacy due to limitation in the delivery system. This study aims to explore the delivery system in the form of liposomes-DNA and chitosan-DNA nanoparticles for DNA vaccine delivery. The making of chitosan-DNA nanoparticles using complex coarsevation method with the ratio of DNA and chitosan mass is 1: 0.5; 1: 1,0; 1: 2,0; and 1: 4,0. Observation of complex formation with gel retardation assay. Liposome-DNA complex was made using LipofectamineTM 3000. In vitro tests were carried out on HeLa cells with a confluent rate of 70% -90%. Chitosan-DNA nanoparticles and liposome-DNA complex with a total of 8 ?g DNA components were transfected for 4 hours then replaced with new growth media and further incubated for 24 hours and analyzed by eGFP protein glow with confocal microscopy. Chitosan-DNA complex was successfully made and visualized as a band of DNA held in agarose wells. Visualization shows that nanoparticles with a mass ratio of 1: 2 are a minimum ratio of chitosan that can trap the whole plasmid DNA to form polyplex. The delivery is able to show the presence of luminescence under a confocal microscope. Fluorescence on chitosan DNA nanoparticles sample qualitatively tends to be less when compared to luminescence in samples with liposome-DNA treatment. The vaccine vector NTC8685-eGFP through the cationic liposome delivery system and chitosan nanoparticles can enter the HeLa cell (model) so that it can be expressed as eGFP protein. Cationic liposomes qualitatively have a higher effectiveness than chitosan nanoparticles in delivering NTC8685-eGFP plasmids into HeLa cells.